Pelaksanaan Sistem Pengendalian Persediaan Bahan Baku dalam Meningkatkan Hasil Produksi - Rochman, Bagus Ananta Saiful; Waluyowati, Nur Prima (Jurnal Kewirausahaan dan Inovasi, 2024)
The background of this research is the absence of the application of methods in managing coffee ingredient that has caused ingredient undersupply and methods of ingredient order calculation that has made ordering cost and storage cost uncontrollable at Kedai Kopi Neojava, a coffee shop in Malang. EOQ method is useful in suggesting the economic order quantity, optimal purchase frequency, reorder point, and safety stock. The objectives of this research are to identify the process of ingredient supply control according to the company’s actual condition and to identify the effects of the application of EOQ method on the total ingredient supply cost at the coffee shop. The data was collected via observations and interviews and was analyzed through EOQ by calculating the Total Inventory Cost, ROP, reorder frequency, and the safety stock. The results of the calculations and analyses indicate that EOQ provides a lower supply cost than the company’s actual method. Further, the former method is also helpful for the company to reduce the impact of demand fluctuation.   Abstrak Latar belakang penelitian ini adalah belum diterapkannya metodeMetode EOQ dapat menunjukkan kuantitas pemesanan ekonomi, frekuensi pembelian optimal, waktu untuk pemesanan ulang (Re-Order Point), dan jumlah persediaan pengamanan (Safety Stock). Tujuan penilitian ini adalah untuk mengetahui proses pengendalian persediaan bahan baku dengan kondisi actual perusahaan dan pengaruh penerapan metode EOQ terhadap total biaya persediaan bahan baku Kedai Kopi Neojava. Pengumpulan data dilakukan dengan menggunakan teknik observasi dan wawancara, sedangkan metode analisis data menggunakan metode EOQ dengan memperhitungkan TIC (Total Inventory Cost), ROP, Frekuensi pemesanan kembali, dan Safety Stock. Hasil perhitungan dan analisis data menggunakan metode EOQ menunjukkan total biaya persediaan yang lebih rendah jika dibandingkan dengan metode Aktual perusahaan. Metode EOQ juga dapat membantu Kedai Kopi Neojava untuk mengurangi pengaruh fluktuatif permintaan yang tidak menentu.